2004
DOI: 10.1016/j.joca.2004.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response relationship for exercise on severity of experimental osteoarthritis in rats: a pilot study

Abstract: This study shows that a calibrated slight or moderate exercise exerts a beneficial influence on the severity of chondral lesions in ACLT rats. Conversely, a strong effort abolishes this chondroprotective effect. This effect could be related to a reduced level of chondrocyte apoptosis through anti-apoptotic capacities of stress-induced Hsp70 overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
122
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 40 publications
11
122
2
2
Order By: Relevance
“…8 In vivo, the beneficial influences produced by moderate exercise in rats subjected to ACLT were manifested by an overexpression of heat shock protein 70 and a decrease in chondrocyte apoptosis. 10 These factors can enhance the defense mechanisms acting against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In vivo, the beneficial influences produced by moderate exercise in rats subjected to ACLT were manifested by an overexpression of heat shock protein 70 and a decrease in chondrocyte apoptosis. 10 These factors can enhance the defense mechanisms acting against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,28 In the standpoint of biomarkers, the running protocol which we set 18 m/min, 30 min/day, three times per 5); (h) medial part of (e) (Â100); (i) lateral part of (f) (Â40); (j) medial part of (g) (Â100).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-intensity exercise has been associated with accelerated OA progression in several animal models (21)(22)(23). However, it has been found that mild to moderate exercise is protective against cartilage damage in the rat ACLT model (21).…”
Section: Acceleration Of Oa Progressionmentioning
confidence: 99%
“…3 HSP70 promotes proteoglycan core protein production in chondrocytes 4 and suppresses chondrocyte apoptosis. 5 In a study employing a rat OA model, Galois et al, 6 found that mild to moderate exercise stress caused excess HSP70 expression in the chondrocyte and suppressed chondrocyte apoptosis. We believe that if HSP70 does indeed protect chondrocytes and could be appropriately expressed in these cells, the protein could be used to inhibit OA progression.…”
mentioning
confidence: 99%